An evaluation of the 'Yaka Ŋarali'' Tackling Indigenous Smoking program in East Arnhem Land: Yolŋu people and their connection to ŋarali'. (6th January 2018) - Tane, Moana P.; Hefler, Marita; Thomas, David P.
Abstract: Issue addressed: Smoking prevalence estimated between 65% and 84% has been reported among the Yolŋu peoples of East Arnhem Land, Northern Territory. We report on findings of an evaluation of the Yaka Ŋarali' Tackling Indigenous Smoking program in East Arnhem Land. Methods: Qualitative interviews with Yolŋu (N = 23) and non‐Yolŋu (N = 7) informants were conducted in seven communities between June 2014 and September 2015, with the support of Cultural Mentors, in homeland communities throughout East Arnhem Land. The data was coded using NVivo software, analysed line‐by‐line and categorised by the researcher (MT) under three a priori categories established as evaluation parameters. In addition, the meanings of ŋarali' and Yolŋu cultural obligations to ŋarali' were analysed using an inductive process. Results: Data were coded under three a priori themes: Yolŋu trying to quit smoking (interest in quitting, access to support); the Yaka Ŋarali program (efficacy and recognition); Yolŋu workforce (roles and responsibilities). Yolŋu informants, including Elders and leaders, both smokers and non‐smokers uniformly acknowledged the deep cultural and traditional connection with ŋarali' attributing this relationship with its introduction by the Macassans and its subsequent adoption into ceremony. Conclusions: Given the strong cultural and traditional connection to ŋarali', care must be taken to ensure tobacco control measures maintain congruence with local values and expectations. So what?: Tailored, localised programs, developed in consultation with communities, Elders and leaders are needed to respect and accommodate the tight connection that the Yolŋu have with ŋarali', maintained over hundreds of years.